(untitled) (East West Medical College Journal, 2024)
Skeletal tuberculosis constitutes about 1j of all cases. Usually, spine and limb bones are involved. Tubercular osteomyelitis of the skull is a rare entity; therefore, diagnosis is rarely suspected. We report one such rare case of an atypical calvaria skull osteomyelitis in a14 years old female who presented with swelling on the right frontoparietal region for 3 months. CT scan of brain and bony window revealed a lytic bony lesion at the right parietal bone with associated epidural soft tissue component at the right parietal top causing compression over adjacent parenchyma- possibly eosinophilic granuloma or chronic osteomyelitis. Patient was treated surgically by excision of the lesion with cranioplasty by synthetic bone cement. After surgical treatment, the specimen was sent for histopathology which showed granulomatous inflammation histologically consistent with tuberculosis. She was treated with antitubercular therapy. Our Case highlights all these aspects of skull tuberculosis with review of the available literature relevant to skull tubercular osteomyelitis. EWMCJ Vol. 12, No. 1&2, January-July 2024: 111-119